Bioactive metallic nanoparticles for synergistic cancer immunotherapy - Lulu Wang; Demin Lin; Muqing Li; Yu Jiang; Yanfang Yang; Hongliang Wang; Hongqian Chu; Jun Ye; Yuling Liu (Acta Pharmaceutica Sinica B)
Cancer immunotherapy has emerged as a promising strategy. However, low response rates and immune-related side effects have plagued immunotherapy. Metallic nanoparticles, utilizing metals as their framework, are gaining prominence in cancer immunotherapy. Metal ions have shown the ability to modulate immune status by activating the cGAS–STING pathway and inducing immunogenic cell death (ICD), thereby enabling multidimensional activation of immunotherapy. Metallic nanoparticles offer significant advantages in cancer immunotherapy, leading to their increasing use in enhancing therapeutic outcomes. In view of the ever-increasing research on metallic nanoparticles, this review presents the construction, characterization, and enhanced cancer immunotherapeutic effects of different types of metal nanosystems from the perspective of the immunoregulatory mechanisms of metal ions. We delve into the current limitations and future directions of metallic nanoparticles in this rapidly evolving field. To the best of our knowledge, this review offers the most up-to-date and systematic analysis of metallic nanoparticles in immunotherapeutic applications. It is anticipated that this review of metallic nanoparticles will inspire a more refined and intelligent design of metallic nanoparticles for future research, paving the way for advancing their clinical applications.